2008
DOI: 10.1111/j.1469-8137.2008.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

A pH signaling mechanism involved in the spatial distribution of calcium and anion fluxes in ectomycorrhizal roots

Abstract: Summary Mycorrhization is a typical example of a host–pathogen symbiotic interaction where the pathogen cell biology and the host immune response coevolved several functional links. Here, the role played by ion fluxes across the root concerning nutrient uptake, osmoregulation, growth and signaling events is addressed. An ion‐selective vibrating probe system was used to determine the net fluxes of protons (H+), calcium (Ca2+) and anions (A−) along nonmycorrhizal and ectomycorrhizal (ECM) roots of Eucalyptus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 91 publications
(134 reference statements)
1
17
0
Order By: Relevance
“…6). Our data agree with the findings of Ramos et al (2009), who reported significant H + efflux from Eucalyptus globulus roots (the apex, meristematic, and elongation zones) colonized with Pisolithus species. The mycorrhiza-stimulated H + efflux is due to the activity of plasma membrane H + -ATPase in the EM associations.…”
Section: Steady and Transient Ion Fluxes In Roots And Em Fungussupporting
confidence: 83%
See 2 more Smart Citations
“…6). Our data agree with the findings of Ramos et al (2009), who reported significant H + efflux from Eucalyptus globulus roots (the apex, meristematic, and elongation zones) colonized with Pisolithus species. The mycorrhiza-stimulated H + efflux is due to the activity of plasma membrane H + -ATPase in the EM associations.…”
Section: Steady and Transient Ion Fluxes In Roots And Em Fungussupporting
confidence: 83%
“…3 canescens roots exhibit increased Ca 2+ enrichment during mycorrhizal symbiosis with P. involutus strain MAJ (Langenfeld-Heyser et al, 2007). Ramos et al (2009) found that EM roots are more efficient than non-EM roots in taking up Ca 2+ from the external medium. Under NaCl stress, Ca 2+ regulates K + /Na + homeostasis in a salt-overly-sensitive3 mutant and wildtype Arabidopsis (Arabidopsis thaliana; Liu and Zhu, 1997).…”
Section: Salt-induced Fluxes Of Hmentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes are considered eletrogenic pumps, because they transport positive charge in the form of H + , generating a difference in charges on either side of the membrane, called membrane potential (MP), and simultaneously generate a difference in the chemical potential of H + or proton concentration gradient (ΔpH) (Yan et al 2002;Ramos et al 2009a). The electrochemical difference produced by this enzyme is used as a driving force in fundamental cellular processes, such as activation of secondary transporters, cellular signaling, nutrient uptake and proton extrusion (Palmgren 2001).…”
Section: Physiological Basis For Iron Uptake By Plantsmentioning
confidence: 99%
“…In general, it is currently possible to use the SIET or MIFE system to measure net fluxes of ions (such as H + , Ca 2+ , K + , Na + , Cl − , Mg 2+ , NH 4 + , NO 3 − , Cd 2+ ) as well as gaseous molecules (such as O 2 and NO) and other compounds (indoleacetic acid, IAA) in real time in various biological systems (Pineros et al 1998;McLamore et al 2009;Wu et al 2010;Ramos et al 2009;Mancuso et al 2005;Mancuso et al 2000). To our knowledge, only a Cd 2+ liquid-membrane ion selective microelectrode (ISME) was routinely applied in the root system (Pineros et al 1998;Farrell et al 2005;Li et al 2012), although several other heavy metal ions (e.g.…”
Section: Introductionmentioning
confidence: 99%